Motorways, tolls and road safety: Evidence from Europe - Daniel Albalate; Germà Bel (SERIEs - Journal of the Spanish Economic Association, 2012)
European governments are increasingly committed to road safety, due to the impact of road accidents in terms of economic loss and as a public health threat. In addition to regulation, providing better road infrastructure is an essential strategy to promote road safety. This paper investigates the relationships between different types of road quality and their impact on national safety outcomes using an international (European) panel data. Since European countries have different motorway network funding strategies-free motorways funded by the budget and tolled motorways funded by users-we pay special attention to the type of funding chosen and consider whether it has any consequences for safety. Our results suggest that extending the motorway network is associated with a reduction in fatality rates, while the rest of road types do not have the same positive effects. However, this virtue is only statistically significant for free motorways; tolled motorways do not provide any significant impact, probably due to socially inefficient pricing and investment policies currently in force.
Keywords: H23; I18; R48; 330; road safety; tolls; motorways and transportation; Straßenverkehrsunfall; Straßenverkehrssicherheit; Straßenbenutzungsgebühr; EU-Verkehrspolitik; EU-Staaten